(untitled) (Homoeopathy for All, 2022)
Awareness of homoeopathy increased after COVID. It is felt across the levels of the homoeopathic supply chain from the doctors, retailers, distributors, whole-sellers and manufacturers. In this scenario, industry-academia collaborations will help the whole homoeopathic field for better-trained homoeopaths, better quality products, a better educational environment, and better industrial growth. This article helps understand the ways and means of academic development through industry participation from our own experience at Schwabe India.